2018
DOI: 10.1002/pri.1749
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapy practice in intensive care units in Jordanian hospitals: A national survey

Abstract: The study showed the main barriers to ICU physical therapy practice in Jordan. There is a need for well-structured strategies to overcome these barriers to help improve the delivery of physical therapy services in Jordan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…The main themes underlying the questionnaires varied between the questionnaires, though the themes, “attitude,” “knowledge,” and “behavior” regarding early mobilization were frequently mentioned (Anekwe et al, 2017; Choong et al, 2013; Goodson et al, 2018; Jolley et al, 2014; Kim et al, 2018; Koo et al, 2016). Furthermore, in three questionnaires (Al-Nassan et al, 2019; Bakhru et al, 2015; Malone et al, 2015) the themes “staffing patterns,” “practices,” and “protocols” were incorporated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The main themes underlying the questionnaires varied between the questionnaires, though the themes, “attitude,” “knowledge,” and “behavior” regarding early mobilization were frequently mentioned (Anekwe et al, 2017; Choong et al, 2013; Goodson et al, 2018; Jolley et al, 2014; Kim et al, 2018; Koo et al, 2016). Furthermore, in three questionnaires (Al-Nassan et al, 2019; Bakhru et al, 2015; Malone et al, 2015) the themes “staffing patterns,” “practices,” and “protocols” were incorporated.…”
Section: Resultsmentioning
confidence: 99%
“…Face validity was excellent in six questionnaires based on the use of the clinical sensibility format (Anekwe et al, 2017; Choong et al, 2013; Koo et al, 2016) or on experts performing a structured evaluation related to what the questionnaire intended to measure (Bakhru et al, 2015; Goodson et al, 2018; Kim et al, 2018). Five other questionnaires (Al-Nassan et al, 2019; Castro et al, 2015; Dafoe et al, 2015; Jolley et al, 2014; Malone et al, 2015) had moderate face validity (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the PTs responded that they learnt ICU PT management from their seniors and coworkers. Research conducted in Jordan reported that the main barriers were inadequate training, insufficient staffing, inadequate perceived importance, and consultation with the PTs working in ICU [ 28 ]. A similar trend was reported in Sri Lanka regarding inadequate staffing and training in ICU among PTs [ 29 ].…”
Section: Discussionmentioning
confidence: 99%